Evaluating CNVII Recovery after Reconstruction with Vascularized Nerve Grafts: A Retrospective Case Series. Issue 1 (January 2021) - Hatchell, Alexandra C.; Chandarana, Shamir P.; Matthews, Jennifer L.; McKenzie, C. David; Matthews, T. Wayne; Hart, Robert D.; Dort, Joseph C.; Schrag, Christiaan H.; Harrop, A. Robertson
Abstract : Summary: Few studies have evaluated vascularized nerve grafts (VNGs) for facial nerve (CNVII) reconstruction. We sought to evaluate long-term outcomes for CNVII recovery following reconstruction with VNGs. A retrospective review of all patients at a tertiary centre who underwent radical parotidectomy and immediate CNVII reconstruction with VNGs was performed (January 2009–December 2019). Preoperative demographics, perioperative factors (flap type, source of VNGs), and postoperative factors [complications, adjuvant therapy, revisionary procedures, length of follow-up, and CNVII function via the House-Brackmann scale (HB)] were collected. Data were summarized qualitatively. Twelve patients (Mage = 53 ± 18 years) with a mean follow-up of 33 (± 23) months were included. Six patients underwent reconstruction with a radial forearm flap and dorsal sensory branches of the radial nerve. Six patients underwent reconstruction with an anterolateral thigh flap and only deep motor branches of the femoral nerve to the vastus lateralis (n = 4) or combined with the lateral femoral cutaneous nerve (n = 2). Two patients regained nearly normal function (HB = 2). Eight patients regained at least resting symmetry (HB = 3 for n = 7; HB = 4 for n = 1). One patient regained a flicker of movement (HB = 5). One patient did not regain function (HB = 6). Six patients had static revision procedures to improve symmetry. Five patients had disease recurrence; 3 died from their disease. VNGs offer a practical and viable addition to the CNVII reconstruction strategy, and result in good functional recovery with acceptable donor site deficits. The associated adipofascial component of these flaps can also augment the soft tissue defect left after tumor ablation.